Partial corn replacement by glycerin and vegetable oils (cashew and castor) as alternative additive in the diets of crossbred bulls finished in a feedlot: Carcass characteristics and Longissimus lumborum muscle evaluation (Research, Society and Development, 2022)
This work was carried out to study the effects of corn grain replacement with glycerin (812 g of glycerol per kg/DM) and vegetable oils (cashew and castor) on the carcass characteristics and meat quality of Purunã bulls finished in a feedlot. A total of 32 Purunã bulls (¼ Aberdeen Angus + ¼ Caracu + ¼ Charolaise + ¼ Canchim) with a mean age of 12 ± 2.0 months and a mean body weight 206.1 ± 20.0 kg were distributed in a completely randomized design with four diets and eight replications per diet. The four experimental diets were as follows: CONT – basal diet; VOIL –basal diet and addition of vegetable oils (3 g/animal/day); GLYC – basal diet and addition of glycerin (20.1% glycerin on a DM basis); GLVO – basal diet and addition of glycerol (20.1% glycerin in DM basis) and vegetal oils (3 g/animal/day). The GLVO diet improved carcass conformation (+12.8%) in comparison with the CONT and GLYC diets. Likewise, fat thickness and proportion of fat in the carcass were higher in the GLVO group (+25.6% and +14.3%, respectively) versus the CONT group. Diets containing glycerin and vegetable oils increased hot (+5.0%) and cold (+5.1%) carcass weights, in comparison to the CONT diet. Diets containing vegetable oils (VOIL and GLVO) improved (+3.4%) carcass dressing relative to the CONT diet. Inclusion of glycerin and vegetable oils did not affect the Longissimus muscle area (68.0 cm2), texture (4.24 points), marbling (6.68 points), or colour (3.51 points) at 24 h post mortem. Likewise, instrumental colour in terms of lightness (32.4), redness (13.9), yellowness (4.94), chroma (14.8), and angle hue (19.1) at 24 h post mortem were unaffected by diet. Finally, the diet did not affect moisture (26.6%), ash (1.1%), crude protein (21.6%), total lipids (2.2%), WBS (3.1 kgf), TBARS (0.28 mg of MDA per kg of meat) or calories (225.5 kcal/100 g of meat). Thus, up to 20% glycerin on a DM basis and vegetable oils from cashew and castor could be added to the diet of bulls finished in a feedlot for 250 days and fed with a high-density energy diet.